Design of Triple-Band Bandpass Filter Using Cascade Tri-Section Stepped Impedance Resonators - Gunawan Wibisono; Teguh Firmansyah; Tierta Syafraditya (LPPM ITB, 2016)
In this research, a triple-band bandpass filter (BPF) using a cascade tri section step impedance resonator (TSSIR), which can be operated at 900 MHz, 1,800 MHz, and 2,600 MHz simultaneously, was designed, fabricated and evaluated. Advanced Design System (ADS) was used to design and simulate the proposed BPF. The proposed BPF using cascade TSSIR was fabricated on an FR4 substrate with dielectric permittivity, substrate thickness and loss tangent at 4.3, 1.6 mm and 0.0017, respectively. The performance parameters of the proposed BPF were characterized by insertion loss, return loss, voltage standing wave ratio (VSWR) and group delay. The performance results from the simulation were compared to those of the fabricated BPF. The results showed that the performances from both the simulated and the fabricated BPF satisfied the design specifications and were in close agreement with each other. Furthermore, the results indicated that the proposed BPF using cascade TSSIR performed better than a hairpin BPF with TSSIR.